Environmental monitoring - Awange, Joseph (2018)
© Springer International Publishing AG 2018. Environmental monitoring has been defined as the observation and study of the environment. This entails objective observations that produce sound data, which in turn provide valuable information that is useful, e.g., in supporting the protection of public water supplies, hazardous, non-hazardous, and radioactive waste management, natural resource protection and management, weather forecasting, and global climate change (Artiola et al, Environmental monitoring and characterization, 2004, [1]) studies. From such a definition, what exactly does the term “monitoring” mean within an environmental perspective? Is it synonymous to measuring or observing? A sound definition of monitoring is essential at this point so as to clearly understand the theme of this book, which intents to highlight the uses of GNSS (Global Navigation Satellite Systems) satellites, which have at times been largely regarded as military assets, to monitor the environment. This can be achieved by using GNSS signals to measure and observe changes in the environment.